Multi-Targeted Anticancer Activity of Imidazolate Phosphane Gold(I) Compounds by Inhibition of DHFR and TrxR in Breast Cancer Cells - Galassi, Rossana; Luciani, Lorenzo; Gambini, Valentina; Vincenzetti, Silvia; Lupidi, Giulio; Amici, Augusto; Marchini, Cristina; Wang, Junbiao; Pucciarelli, Stefania (Frontiers in Chemistry, 2021)
Gold(I) compounds with the structural framework of N-Au-P moiety, having pyrazole or imidazole and triphenylphophane as ligands, have been found to be cytotoxic on the regards of several cancer cell lines and also against cisplatin or Multi-Drug Resistant cancer cells. Among this kind of molecules, according to an overall solubility in polar media and a quite good stability, some imidazolate or pyrazolate gold(I) phosphane derivatives have been selected for MTT tests in SKBR3, A17 and MDA-MB231 cancer cells, representing aggressive breast cancer subtypes (HER2-positive and basal like breast cancer, respectively). The MTT tests demonstrated that 4,5-dicyano-imidazolate-1yl-gold(I)-(triphenylphosphane) and 4,5-dichloro-imidazolate-1yl-gold(I)-(triphenylphosphane) compounds were able to decrease cell viability in a dose-dependent manner with IC50 values at low M concentrations with the most active one with a value of about 3.46 M in MDA-MB231 cells treated for 48 h. Moreover, being dihydrofolate reductase, DHFR, an enzyme largely involved in cell proliferation, the residual enzymatic activity of DHFR has been measured in breast cancer cells treated with these two gold-compounds for 4 or 12 hours in comparison with control cells. The activity of DHFR was significantly reduced in both SKBR3 and A17 cells by 4,5-dicyano-imidazolate-1yl-gold(I)-(triphenylphosphane) and 4,5-dichloro-imidazolate-1yl-gold(I)-(triphenylphosphane). Despite the strong cytotoxic activity of gold complexes in human MDA-MB231 cells, their effect did not result in a strong inhibition of DHFR activity at 12 hours and, interestingly, it was remarkably high after 4 hours of treatment. The DHFR inhibition data have been compared to those obtained with the undisputed molecular target for gold compounds, the thioredoxine reductase, TrxR. As expected, this enzyme was inhibited in breast cancer cell lines treated with the selected gold-compounds. In particular, an inhibition of its activity was observed with 37% and 49% of residual activities for the match of SKBR3 cells and 4,5-dicyano-imidazolate-1yl-gold(I)-(triphenylphosphane) or 4,5-dichloro-imidazolate-1yl-gold(I)-(triphenylphosphane), respectively. Additionally, the biological properties of the gold complexes including their binding to calf thymus DNA (Ct-DNA) have been investigated by UV-Vis, fluorescence spectroscopy for competitive binding studies with ethidium bromide (EB), and 4',6-diamidin-2-fenilindolo (DAPI) as also the possible interaction of the same compounds with -plasma protein as BSA and ATF.